CORRELATION BETWEEN EXPLOSIVE POWER LEG MUSCLE WITH AGILITY TO THE ABILITY OF FRONT KICK ON PENCAK SILAT ATHLETE PPLP PEKANBARU RIAU - Ramadi UNRI; Kristi Agust; Robby Septian (Jurnal MensSana, 2016)
Based on observation, researchers found front kick ability of pencak silat athletes were low. Factors that influence this finding was physical condition such as explosive power leg mucle and agility. The aim of this research is to find out the correlation between explosive power leg muscle with agility to the ability of front kick on pencak silat PPLP Pekanbaru Riau Province. The instrument of this study were Jump MD for explosive power muscle leg, agility using shuttle run and front kick ability test. We performed total sampling of 10 athletes of Pencak Silat PPLP Pekanbaru Riau Province. We used the product moment correlation analisys test, the level of significance of α = 0.05. Based on research and data analysis then relationship which mean together of muscle leg explosive power and agility with the ability of front kick pencak silat PPLP Pekanbaru Riau Province the results showed Fhitung (4.422) < Ftabel (4.74) and Rhitung (0.747) with stronger category for interpretasi table.